Structural causes and prevalence of neurosensoral hearing loss in children in Samarkand region - Djurabekova Aziza; Abdullayeva Nargiza; Samatov Farrukh (Research Parks Publishing LLC, 2020)
According to the WHO, hearing loss occurs in 3% of children, of which 0.03% are children with severe and profound sensorineural hearing loss. Persistent hearing impairment in children is a serious problem for the child population. Chronic sensorineural hearing loss in children is the focus of many researchers. The factors affecting the organs of hearing of a growing organism do not decrease; in modern conditions, they acquire more and more importance (l). The vast experience of complex therapy for hearing loss in children has a character of insufficient effectiveness, which predetermines the search for new non-drug methods of treatment, the development of new approaches to the social adaptation of children with hearing loss. Hearing impairment of a child leads to impaired speech and mental development. Early diagnosis of hearing disorders and adequate rehabilitation can prevent a child's psycho-speech deviation (l).